Sperm alterations in the Vesper mouse Calomys laucha exposed to soil contaminated with crude oil - de Almeida, Krissia Aparecida (2018)
Calomys laucha (small vesper mouse) is a small wild rodent that lives in the southern coastal dunes of Brazil, where it feeds and builds nests for breeding, and this lifestyle makes it susceptible to the impacts of human activities in coastal and marine regions. This study aimed to evaluate the some reproductive parameters of C. laucha males in a simulated oil spill. The animals were exposed for 14 days to artificial soil contaminated by petroleum in different concentrations (0, 1, 2, 4 and 8% v / v) and after this period the animals were killed and the testis and epididymis removed for analysis. Exposure did not affect the weight of the testes, but it caused a decrease in sperm viability and an increase in the presence of sperm abnormalities, in particular the “lasso-like fold” anomaly (in this case a dose-dependent effect). This study demonstrated that exposure to soil contaminated by crude oil causes damage to the spermatozoa of C. laucha, which may influence the fitness of populations of this species.